2015
DOI: 10.5455/jice.20141020064838
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidant activity and phytochemical constituent of two plants used to manage foot and mouth disease in the Far North Region of Cameroon

Abstract: Aim:Plants used in the Far North Region of Cameroon by livestock farmers to manage foot and mouth disease (FMD) in cattle and the phytochemical composition and antioxidant potentials of two of them (Boscia senegalensis [BS] and Tapinanthus dodoneifolius [TD]) were investigated in this study.Materials and Methods:Ethno veterinary data were collected from 325 livestock farmers using semi-structured interviews from September 2011 to April 2012. The 2,2-diphenyl-picrylhydrazyl radical scavenging activity and total… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
13
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(17 citation statements)
references
References 26 publications
2
13
2
Order By: Relevance
“…Recent studies on the antioxidant activity of Boscia demonstrated their high antioxidant activity potential [2]. Unfortunately we did not found significant correlation between the phenols and neither the DPPH scavenging activity (r = -0.17) or the total reducing power (r = 0.11).…”
Section: Discussioncontrasting
confidence: 45%
See 2 more Smart Citations
“…Recent studies on the antioxidant activity of Boscia demonstrated their high antioxidant activity potential [2]. Unfortunately we did not found significant correlation between the phenols and neither the DPPH scavenging activity (r = -0.17) or the total reducing power (r = 0.11).…”
Section: Discussioncontrasting
confidence: 45%
“…One active principle in Boscia has been identified as a glucocapparin, a sulfonated glucose which exhibited not only hypoglycemic effect, but also cytotoxicity [3]. It is demonstrated that Boscia is rich in phenols and antioxidant properties [2], and these molecules may also justify the use of Boscia in traditional medicine. Traditionally the decoction used in patient treatment consisted of mixing the seed powder (about 200 g) with water (about 1L) followed by boiling for about 30 min.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The fact that drugs are administered by trained veterinarians in the ranch suggests that the prophylactic failure may lie either on the repeated use of the same molecules of trypanocide [ 28 , 29 ] and/or on the quality of drug used. Vougat et al [ 30 ] reported that many veterinary medicines in the market and veterinary pharmacies are not up to the standards required in north Cameroon. This fact presumes that the risk for the development of drug resistance is likely higher among traditionally managed livestock where the majority of pastoralists administer drugs without any parasitological diagnosis or even clinical examination [ 31 ] and without respect of drug prescription [ 30 , 32 , 33 ].…”
Section: Discussionmentioning
confidence: 99%
“…The biophysical characteristics of this study area are as described in our previous paper (Vougat et al 2015). Generally, the region is dry with a rainy season from June to November.…”
Section: Study Areamentioning
confidence: 99%